Pengaruh Pelatihan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Esteh Bogor - Yogi Rizki Nugraha, Sinta Sundari; Endang Silaningsih; Palahudin Palahudin (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of job training and work discipline on employee performance at PT Esteh Bogor. The main focus of the study is to identify the extent to which these two independent variables, either simultaneously or partially, can influence employee performance achievement. The population in this study were all employees of PT Esteh Bogor, with a sample size of 100 people selected purposively. The method used was quantitative research with a descriptive and verification approach. Data analysis was conducted using multiple linear regression to examine the relationship and influence between job training (X₁), work discipline (X₂), and employee performance (Y). Primary data were collected through questionnaires that had been tested for validity and reliability, while secondary data were obtained from company documents. The results of the study indicate that, first, job training and work discipline simultaneously have a positive and significant effect on employee performance. This means that improving the quality of training provided by the company, accompanied by the consistent implementation of work discipline, will have an impact on increasing employee productivity and work effectiveness. Second, job training partially has a positive effect on employee performance. These findings indicate that relevant, structured, and job-appropriate training can improve employee competence, skills, and motivation. Third, work discipline also has a partial positive effect on employee performance, indicating that compliance with regulations, punctuality, and consistency in carrying out tasks are important factors in achieving optimal work targets. Overall, this study confirms that a company's success is not only determined by technical skills acquired through training, but also by a disciplined work attitude. Therefore, the management of PT Esteh Bogor is advised to continue improving the quality of its training programs and enforcing work discipline rules fairly and consistently, in order to create maximum and sustainable employee performance.